COMPARISON OF LIMB SALVAGE WITH MEGA PROSTHESIS VERSUS AUTO GRAFT RECONSTRUCTION AFTER CRYOTHERAPY IN LIMB SARCOMA PATIENTS - ZIA , OB; SHAFI , MK; RAZA , T; KHALIL , MT; ALI , U; ABIDI , SAR; AKHTAR , N (Biological and Clinical Sciences Research Journal, 2023)
Osteosarcoma is the most common primary malignant bone tumor, with children and adolescents being the most at-risk population. It accounts for 2% of all childhood tumors. The main goal of this study was to compare the use of limb salvage with mega prosthesis versus auto graft reconstruction after cryotherapy in patients with limb sarcoma. This retrospective study was conducted at Liaquat College of Medicine and Dentistry Darul Sehat Hospital Karachi from June 2023 to August 2023. The data was collected with the permission of the hospital’s ethical committee. A standard uniform management protocol was adopted for each case. All patients were skeletally immature, with the predicted overall growth of less than 3 cm calculated using the Multiplier method. The data was collected from 45 patients with a mean age of 13.8±4.6 years. The predominant type of tumor was Osteosarcoma (77.14%) followed by Ewing Sarcoma and Chondrosarcoma. Five patients required a more extended hospital stay after mega prosthesis as compared to the other group. It is concluded that patients with limb sarcomas treated with Mega prosthesis had better functional outcomes than those treated with autograft reconstruction after cryotherapy.